In situ normothermic perfusion of livers in controlled circulatory death donation may prevent ischemic cholangiopathy and improve graft survival. Issue 6 (1st February 2019) - Watson, Christopher J. E.; Hunt, Fiona; Messer, Simon; Currie, Ian; Large, Stephen; Sutherland, Andrew; Crick, Keziah; Wigmore, Stephen J.; Fear, Corrina; Cornateanu, Sorina; Randle, Lucy V.; Terrace, John D.; et al.
Abstract : Livers from controlled donation after circulatory death (DCD) donors suffer a higher incidence of nonfunction, poor function, and ischemic cholangiopathy. In situ normothermic regional perfusion (NRP) restores a blood supply to the abdominal organs after death using an extracorporeal circulation for a limited period before organ recovery. We undertook a retrospective analysis to evaluate whether NRP was associated with improved outcomes of livers from DCD donors. NRP was performed on 70 DCD donors from whom 43 livers were transplanted. These were compared with 187 non‐NRP DCD donor livers transplanted at the same two UK centers in the same period. The use of NRP was associated with a reduction in early allograft dysfunction (12% for NRP vs. 32% for non‐NRP livers, P  = .0076), 30‐day graft loss (2% NRP livers vs. 12% non‐NRP livers, P  = .0559), freedom from ischemic cholangiopathy (0% vs. 27% for non‐NRP livers, P  < .0001), and fewer anastomotic strictures (7% vs. 27% non‐NRP, P  = .0041). After adjusting for other factors in a multivariable analysis, NRP remained significantly associated with freedom from ischemic cholangiopathy ( P  < .0001). These data suggest that NRP during organ recovery from DCD donors leads to superior liver outcomes compared to conventional organ recovery. Abstract : In situ normothermic regional perfusion of controlled DCD liver donors is associated with significant improvement in early allograft function, fewer graft failures within 30 days, and freedom from ischemic cholangiopathy compared to a contemporaneous comparator group.